Preparation and self-assembly behavior of polystyrene-block-poly (dimethylaminoethyl methacrylate) amphiphilic block copolymer using atom transfer radical polymerization (eXPRESS Polymer Letters)
Asymmetric and semi-symmetric amphiphilic diblock copolymers polystyrene-block-poly (dimethylaminoethyl methacrylate) (PS-b-PDMAEMA) with the same PS block length of 62 repeat units and quite short (3 repeat units) or equivalent (47 repeat units) length of PDMAEMA have been prepared simply by varying the ratio of the bromine-terminated macroinitiator polystyrene (PS-Br) to DMAEMA using atom transfer radical polymerization (ATRP). The chemical structures and compositions of the PS-b-PDMAEMA block copolymers are studied by nuclear magnetic resonance (NMR) spectroscopy, gel permeation chromatography (GPC), and elementary analysis (EA). The self-assembly behaviors of copolymers in N,N-dimethyl formamide (DMF) with different pH and dioxane/water binary solvent mixture by direct dissolution method (DD), are studied by transmission electron microscopy (TEM), electron diffracting analysis (EDA), and energy-dispersive analysis of X-rays (EDAX) techniques. Transmission electron microscopy results suggest that asymmetric block copolymer PS62-b-PDMAEMA3 (the numbers in the form of footnotes represent repeated units of each monomer in the copolymer) can form spherical core-shell micelles, large compound reverse micelles (LCRMs), hexagonal/rhombic phases, reverse hexagonal/rhombic phases, vesicles, reverse vesicles and necklace-like reverse micelles, controlled by common or selective solvent and pH, while most of the aggregates of semi-symmetric PS62-b-PDMAEMA47 are simply spherical, such as spherical core-shell micelles and reverse spherical core-shell micelles, besides hexagonal/rhombic phases. All above structures are controlled by three components of the free energy of aggregation: core-chain stretching, interfacial energy and intercoronal chain interaction.